Life together in the way of Jesus Christ: an introduction to Christian theology - Stiver, Dan R. (Baylor University Press, 2009)
Beginning the journey -- Prolegomena : mapping the journey -- The doctrine of revelation : lighting the way -- The doctrine of God : the beginning and the end -- The doctrine of creation : the beginning -- The doctrines of humanity and sin : rising and falling -- The doctrine of Christ : the light of the way -- The doctrine of salvation : the way -- The doctrine of the church : walking together -- The doctrine of the last things : the end